Pain outcomes in children who received intrathecal vs intravenous opioids for pain control following major urologic surgery: a retrospective review. Issue 12 (15th October 2015) - Putnam, Elizabeth M.; Koppera, Prabhat; Malviya, Shobha; Voepel‐Lewis, Terri
Summary: Background: Intrathecal (IT) opioid administration has been associated with postoperative benefits including reduced pain and opioid use in children. However, the postoperative benefits and risks of IT opioid administration during major urologic surgery in children remain unclear. Aim: The aim of this study was to compare postoperative pain and adverse event outcomes among children who received IT vs intravenous (IV) opioids during major urologic surgery. Methods: We reviewed the medical records of children 3–17 years of age who underwent ureteroneocystostomy or pyeloplasty between 2006 and 2012. Electronically captured anesthetic and surgical data, postanesthesia care recovery unit (PACU) and nursing flowsheets, and daily progress notes through hospital discharge were reviewed. Analgesic techniques (i.e., IT or IV patient/nurse controlled opioids), all analgesic drugs and doses were recorded. Outcome measures included pain scores, need for rescue analgesics, opioid‐related adverse events, and their treatments. Results: Seventy‐seven children received IT opioids and 51 received IV opioids. More children in the IV group required rescue analgesics and had higher pain scores at PACU discharge. Children in the IV group required rescue opioids more frequently than the IT group from 0 to 8 h and 8 to 16 h after PACU discharge, but rates were similar by 16–24 h 70% of children in IT group transitioned directly to oral opioids. Seven IT placements were considered as failed due to early need for rescue opioids. Four (8%) of the IV group and seven (9%) of the IT group experienced oxygen desaturation. Two of these, both in IT group required naloxone and one was admitted to ICU for observation. The IT group experienced a higher incidence of pruritus, constipation and hypotension. Conclusion: We observed better postoperative pain control in children who received IT vs IV opioids for the first 16 h with no discernible difference thereafter. The intrathecal group experienced higher incidences of pruritus, constipation, and hypotension. Abstract :